Burn and cancer risk: A state-wide logitudinal analysis - Duke, Janine; Rea, S.; Semmens, James; Edgar, D.; Wood, Fiona (Elsevier, 2011)
Background: Major burn can lead to impairment of the immune system and individuals who experience chronic immunosuppression are at a greater risk of developing a malignancy. Examination of prospective long term follow-up data to clarify the risk of cancer in this patient group is important. Methods: Linked hospital morbidity records of 23,450 persons admitted with an index burn in Western Australia from 1983 to 2008 were merged with cancer and death data. The cancer incidence of those hospitalised for burn was compared to the general population of Western Australia. Poisson regression was used to assess the impact of burn severity and skin graft on cancer risk. Results: From 1983 to 2008, there were 759 notifications of cancer (standardised incidence ratio (SIR), 95% confidence interval (CI): 0.97, 0.90–1.04). For the cohort admitted 1983–2008, a significant decrease in cancer risk for males (SIR, 95%CI: 0.90, 0.83–0.99), and a non-significant increase in cancer risk for females (SIR, 95%CI: 1.12, 1.00–1.28) were estimated. For the sub-cohort admitted 1983–1987 with optimum follow-up, incidence of cancer was significantly less for males (SIR, 95%CI: 0.86, 0.75–0.99), while a significant increase in risk of cancer for females (SIR, 95%CI: 1.39, 1.15–1.69) was estimated. Conclusions: There appears to be a gender effect in relation to incidence of cancer after burn. The risk of cancer for females hospitalised for burn during 1983–1987, with optimum follow-up time, was significant and increased in magnitude to 39% greater incidence of all-cause cancer than that for females in the general population of Western Australia.